1997
DOI: 10.1093/protein/10.5.511
|View full text |Cite
|
Sign up to set email alerts
|

Molecular modelling of the nicotinic acetylcholine receptor transmembrane region in the open state

Abstract: A model of the nicotinic acetylcholine receptor transmembrane region has been constructed which may represent the channel in its open-state. The positions of helices flanking the ion channel match those observed by electron microscopy and previously reported by others. Residues labelled, mutated or by other means known to have a strong influence on ion flux are each accessible from the lumen of the modelled channel. The model provides new insights into our current understanding of the ion channel structure, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

1997
1997
2007
2007

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 10 publications
0
23
0
Order By: Relevance
“…The conception of hydrophilic residues lining the pore is based on experimental findings in the pore-lining helices of the nicotinic acetylcholine receptor (nAChR) (38)(39)(40)(41). Computational studies have used these findings to generate not only equivalent bundles of M2 from nAChR (31,32) but also bundles of the TM domain of the influenza A channel protein M2 (33) and the channel protein NB from influenza B (34). However, recent studies also show that the positioning of tryptophans toward the center of the pore can result in a model representing a stable "closed" structure (21,24,42).…”
Section: Discussionmentioning
confidence: 99%
“…The conception of hydrophilic residues lining the pore is based on experimental findings in the pore-lining helices of the nicotinic acetylcholine receptor (nAChR) (38)(39)(40)(41). Computational studies have used these findings to generate not only equivalent bundles of M2 from nAChR (31,32) but also bundles of the TM domain of the influenza A channel protein M2 (33) and the channel protein NB from influenza B (34). However, recent studies also show that the positioning of tryptophans toward the center of the pore can result in a model representing a stable "closed" structure (21,24,42).…”
Section: Discussionmentioning
confidence: 99%
“…For example, in simulations of docking interactions with the a7 nAChR, pentobarbital appears to primarily dock at ring 15, 35 while other ligands primarily bound to serine (S ring, position 8) and threonine (T ring, position 4), see Figure 1, with only minor interactions with the V ring. 36 …”
Section: A the Luminal-binding Sitementioning
confidence: 99%
“…5A and B) and is consistent with previous docking studies with the a7 nAChR which indicate that the S at position 8 plays a role in the ligand binding. 36 Dextromethorphan (DM) and LM were chosen for the initial docking studies based upon previous functional, chromatographic, and thermodynamic studies, which demonstrated that these enantiomers bind enantioselectively to the a3b4 nAChR and that the observed differences were due to an enhanced stability of the DM-a3b4 nAChR complex. 20,41 In the docking simulations, the lowest energy docked conformations of the DM and LM complexes were located at the V/F ring and involved the insertion of the hydrophobic portion of both molecules into the hydrophobic cleft found at this position ( Fig.…”
Section: Nci Docking In the A3b4 Nachr Luminal Domainmentioning
confidence: 99%
“…The molecular surface displays a crevice or cavity at the level of Thr 422 (arrows). The hypothetical model of the aM4 was drawn using the theoretical modelling coordinates employed in Ortells et al (1997) and the software WebLab Viewer (surface potential, solvent-accessibility rendering mode) from Molecular Simulations, Inc. mutant AChR behaved like the quadruple mutant, whereas the other three were indistinguishable from the wild-type. It was concluded that Thr 422 , a residue close to the extracellular-facing membrane hemilayer in aM4, has direct bearing on the changes in hydrocortisone sensitivity and propose its involvement in the steroid-AChR interaction site (Garbus et al 2002).…”
Section: Putative Steroid Sites At the Achr Transmembrane Regionmentioning
confidence: 99%
“…The two 3-D models were drawn using the software WebLab Viewer from Molecular Simulations, Inc. The lower panel shows a hypothetical representation of the AChR transmembrane region (coordinates were obtained from Dr Marcelo Ortells, see also Ortells et al (1997)). The model reproduces faithfully the overall shape and dimensions of Unwin's (1995) medium-resolution electron microscopy images of the AChR transmembrane domain.…”
Section: Introductionmentioning
confidence: 99%